Population health trends and disease profile in Somalia 1990-2019, and projection to 2030: will the country achieve sustainable development goals 2 and 3? - Joana Morrison; Sk Md Mamunur Rahman Malik (BMC, 2023)
Abstract Objectives This study aims to evaluate whether Somalia will reach Sustainable Development Goals 2 and 3 by 2030 and what the country requires to advance closer to these objectives. Setting: Somalia. Participants We carried out analyses of secondary data obtained from the following open-access databases: Global Burden of Disease 2019 study; United Nations (UN) Department of Economic and Social Affairs Population Division; World Bank World Development Indicators; United Nations Children's Fund (UNICEF); UNICEF/World Health Organisation (WHO)/World Bank Joint Child Malnutrition Estimates; and UN Interagency Group for Child Mortality Estimation (UN IGME), disaggregated by sex. Primary outcome measures: stillbirth, neonatal, infant, under-five, maternal and child mortality; under-five malnutrition; life expectancy; health-adjusted life expectancy; age-standardised all-cause mortality; age-standardised cause-specific mortality for the leading causes of death; disability-adjusted life years. Secondary outcome measures: vitamin A coverage; stunting, overweight in children under 5; top risk factors contributing to cause-specific mortality. Results life expectancy in Somalia will increase to 65.42 years (95% UI 62.30-68.54) for females and 58.54 years (95% UI 54.89-62.19) for males in 2030. Stunting will continue to decline to 25.2% (90% UI 13.9-39.5%), and the under-five mortality rate will drop to 85.9 per 1000 live births (90% UI 22.0-228.1 per 1000 live births) for females and 96.4 per 1000 live births (90% UI 24.8-255.3 per 1000 live births) for males in 2030. This study's analyses predict that the maternal mortality ratio in Somalia will decline to 696.42 deaths per 100,000 live births in 2030. Conclusions there has been progress towards SDG targets in Somalia since 1990. To achieve these, Somalia requires greater health improvements than observed between 1990 and 2019.